Analisis Penggunaan Gaya Bahasa Dalam Novel “Laut Bercerita” Karya Leila S. Chudori - Syakila Nur Haliza (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The novel is a popular literary work and much-loved by teenagers to adults. The novel also uses everyday language and also uses a beautiful style of language so that it makes its readers feel as if they are immersed in the story of the novel. Language style is the selection or use of figurative words that are arranged beautifully in a sentence that is useful for giving the impression of feelings and implied meanings. This study aims to determine the use of any language style contained in the novel entitled "Laut Bercerita" written by Leila S. Chudori. In this study using a type of descriptive qualitative method. Collecting data in this research uses observation, note-taking and documentation study techniques. Based on the results of the analysis in this study, it was found that several types of language styles were always used by the author, namely personification language style, sarcasm language style, hyperbole language style, simile language style, and metaphorical language style